Posouzení informačního systému firmy a návrh změn - Červený, Benjamín (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Táto diplomová práca sa zameriava na analýzu informačného systému vybranej spoločnosti a návrhu zmien. Na základe analýzy súčasného stavu boli navrhnuté zmeny, ktoré by mali výrazne prospieť k vyhodnocovaniu marketingových kampaní a automatizácií podnikových činností.

This thesis focuses on the analysis of the information system of the selected company and the proposed changes. Based on the analysis of the current situation, changes have been proposed that should significantly benefit the evaluation of marketing campaigns and automation of business activities.
Information System Assessment and Proposal of ICT Modification
Keywords: Informačný systém; Business Intelligence; SLEPT analýza; SWOT analýza; riadenie rizík; Google Data Studio; IFTTT; Information system; Business Intelligence; SLEPT analysis; SWOT analysis; risk management; Google Data Studio; IFTTT